Substrate augmented catalytic activity towards NRR: a case study of Li doped Al clusters on defective graphene - Samal, Pragnya Paramita; Poonam; Krishnamurty, Sailaja (2021)
Density Functional Theory (DFT) based methods are applied to examine the potential of lithium doped aluminium clusters consisting of 3-13 atoms for dinitmgen molecule activation in terms of N N bond length, redshift in N N bond stretching frequency, nitrogen interaction energy and frontier molecular orbitals analysis. The present work highlights the role of monovacant C-3 defective graphene as a support in fine tuning the catalytic activity of Li doped Al clusters for reduction of N-2. Fundamental insights to synergic binding of clusters with defective graphene is brought out and its role in enhancing activation of dinitmgen molecule is explained. Supported Aln-1Li clusters with six or more atoms are noted to be more active towards N-2 molecule activation as compared to the clusters without support. Dinitrogen molecule undergoes a maximum bond elongation of 1.56 angstrom corresponding to redshift of 1690 cm(-1) on Al7Li@graphene and Al12Li@graphene. This is maximum value reported in context of activation for N-2 molecule till date.
Keywords: Al clusters; Al12Li; C-3 defective graphene; DFT; Li Doping; N-2 activation; Red-shift